(untitled) (Economics and region, 2024)
This article describes an increasingly popular non-traditional approach to assessing the effectiveness of investment projects under conditions of uncertainty - the fuzzy set method. It is widely agreed that the key factor in analysing the effectiveness of investment projects is the analyst’s ability to predict future values of key financial indicators. The fate of the project, and ultimately the well-being of both the investor and the analyst, depends on how accurately the analyst determines future cash flows, interest rates, company capabilities and flexibility. The paper is devoted to the topical issue of evaluating complex investment projects under conditions of risk and uncertainty. The main methods of risk accounting are considered and their main disadvantages are described in detail. As an alternative method, the author proposes to use the theory of fuzzy sets, which has recently become increasingly popular among specialists in various fields. The publication shows that the theory of fuzzy sets is one of the most effective mathematical theories aimed at processing uncertain information and largely integrates known approaches and methods. The author proposes a mathematical model for calculating the risks of investment projects based on fuzziness theory.